The effect of neurofeedback training for sport performance in athletes: A meta-analysis - Xiang, M.-Q.; Hou, X.-H.; Liao, B. G.; Liao, J. W.; Hu, M. (Psychology of Sport and Exercise, 2018)
Objectives: This meta-analysis of randomized controlled trials aimed to assess the effect of neurofeedback training (NFT) on sport performance and electroencephalography (EEG) power in athletes. Method: A computerized search of Web of Science, PsycINFO and PubMed was performed to identify relevant studies, published 1990 through February 1, 2017. The outcome measures were sport performance and EEG power. Two review authors identified eligible studies and extracted data independently. The quality of the included studies was assessed with the Cochrane Risk of Bias tool. Standard mean differences (SMDs) and 95% confidence intervals (CIs) were calculated and pooled using a random effects model. Results: A total of 10 randomized controlled trials (229 athletes) met the inclusion criteria. Significant effects of NFT were found for sport performance (SMD = 0.65, 95%CI=0.28 to 1.03, p = .0006) and EEG power (SMD=0.45, 95%CI=0.09 to 0.80, p = .01). However, the NFT's effect for sport performance was not significantly different when compared to well-controlled trials with active/placebo control (SMD=0.51, 95% CI=-0.27 to 1.30, p = .20). Conclusions: NFT could make athletes change in EEG power and effectively improve sport performance. Effect of NFT for sport performance was moderated by control group design, that is, when analyses were restricted to active/placebo controls, the efficacy NFT applied in sport performance might be rather weak. Future efforts should focus on standard NFT protocols and better-organized trials.